Mass and Angular Momentum Transport in a Gravitationally Unstable Protoplanetary Disk with Improved 3D Radiative Hydrodynamics - Steiman-Cameron, Thomas Y.; Durisen, Richard H.; Boley, Aaron C.; Michael, Scott; Desai, Karna; McConnell, Caitlin R. (The Astrophysical journal, 2023)
During early phases of a protoplanetary disk's life, gravitational instabilities (GIs) can produce significant mass transport, can dramatically alter disk structure, can mix and shock-process gas and solids, and may be instrumental in planet formation. We present a 3D grid-based radiative hydrodynamics study with varied resolutions of a 0.07 M ⊙ disk orbiting a 0.5 M ⊙ star as it settles over most of its radial extent into a quasi-steady asymptotic state that maintains approximate balance between heating produced by GIs and radiative cooling governed by realistic dust opacities. We assess disk stability criteria, thermodynamic properties, strengths of GIs, characteristics of density waves and torques produced by GIs, radial mass transport arising from these torques, and the level to which transport can be represented as local or nonlocal processes. Physical and thermal processes display distinct differences between inner optically thick and outer optically thin regions of the disk. In the inner region, gravitational torques are dominated by low-order Fourier components of the azimuthal mass distribution. These torques are strongly variable on the local dynamical time and are subject to rapid flaring presumably driven by recurrent swing amplification. In the outer region, m = 1 torques dominate. Ring-like structures exhibiting strong noncircular motions, and vortices develop near the inner edge between 8 and 14 au. We find that GI-induced spiral modes erupt in a chaotic manner over the whole low- Q part of the disk, with many spiral modes appearing and disappearing, producing gravitoturbulence, but dominated by fluctuating large-scale modes, very different from a simple α -disk.